DORIAN GRAY- THE SYMBOL OF SIN AND REDEMPTION IN « THE PICTURE OF DORIAN GRAY » BY OSCAR WILDE. - Vũ, Thị Hồng Luyến (2021)
This graduation paper aims to give a close and careful investigation into a small aspect of sin and redemption, the basic theme in the novel “The picture of Dorian Gray” by Oscar Wilde. More specifically, this research is restricted to the sin and redemption symbolized by the leading character Dorian Gray with two major objectives as follow: • To critically analyze the sins Dorian commits in his double life in comparison with other characters’ sins to show that Dorian is the symbol of sin the novel. • To carefully examine Dorian’s redemption for his endless list of sins in comparison with other characters’ redemption to demonstrate that Dorian is also the symbol of redemption in the novel.